2016
DOI: 10.1371/journal.pone.0148903
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular Variability Analysis and Baroreflex Estimation in Patients with Type 2 Diabetes in Absence of Any Manifest Neuropathy

Abstract: IntroductionIndexes derived from spontaneous heart period (HP) and systolic arterial pressure (SAP) fluctuations can detect autonomic dysfunction in individuals with type 2 diabetes mellitus (DM) associated to cardiovascular autonomic neuropathy (CAN) or other neuropathies. It is unknown whether HP and SAP variability indexes are sensitive enough to detect the autonomic dysfunction in DM patients without CAN and other neuropathies.MethodsWe evaluated 68 males aged between 40 and 65 years. The group was compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Although these altered hemodynamic responses are evident in T2DM, the effects of T2DM on the reflexive control of circulation during exercise are not completely understood. Currently, the effects of T2DM on baroreflex control are inconclusive (8,21). However, a recent study reported that patients with T2DM had increased muscle sympathetic nerve activity (MSNA) and augmented blood pressure responses to isometric handgrip exercise, a response which was maintained during post-exercise occlusion, suggesting that the metaboreflex was exaggerated in patients with T2DM (20).…”
Section: Introductionmentioning
confidence: 99%
“…Although these altered hemodynamic responses are evident in T2DM, the effects of T2DM on the reflexive control of circulation during exercise are not completely understood. Currently, the effects of T2DM on baroreflex control are inconclusive (8,21). However, a recent study reported that patients with T2DM had increased muscle sympathetic nerve activity (MSNA) and augmented blood pressure responses to isometric handgrip exercise, a response which was maintained during post-exercise occlusion, suggesting that the metaboreflex was exaggerated in patients with T2DM (20).…”
Section: Introductionmentioning
confidence: 99%
“…Those data showed a decreased vagal tone and an increased sympathetic tone in the SHR, which were partially restored after the treatment with kefir for 60 days [46]. The magnitude of the kefir effect on the autonomic control of the heart was similar to that obtained by other interventions [54,[58][59][60]. The challenge is now to design new studies aiming to determine if the origin of the abnormality is located at central areas or peripheral nerves/receptors.…”
Section: Kefir and Autonomic Neural Control Of Cardiovascular Functionmentioning
confidence: 52%
“…Porta et al [ 16 ] proposed the non linear analysis of short term heart period variability, whose patterns are classified and divided into four families. The non linear analysis can detect nonreciprocal autonomic change [ 16 , 24 , 58 ]. We performed the first non-linear analysis of HRV in leprosy patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the control group has a greater predominance of vagal modulation, a greater HRV, and a greater complexity of cardiac autonomic modulation [ 16 , 24 ]. The change of position from the supine to the sitting position represents a stimulus, especially for the sympathetic modulation [ 14 , 16 , 24 , 58 , 60 ]. In the supine position, both autonomic systems have tonic activity with vagal modulation predominance that caused a high HRV while the sitting position had a sympathetic modulation prevalence and led to the decrease of the HRV [ 37 , 40 ].…”
Section: Discussionmentioning
confidence: 99%